2005
DOI: 10.1158/1078-0432.ccr-04-2102
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Growth Inhibition by Simultaneously Blocking Epidermal Growth Factor Receptor and Cyclooxygenase-2 in a Xenograft Model

Abstract: Purpose: Our previous study revealed that simultaneously targeting epidermal growth factor receptor (EGFR) tyrosine kinase and cyclooxygenase-2 (COX-2) additively or synergistically inhibited growth of squamous cell carcinoma of the head and neck (SCCHN) in vitro. However, an in vivo efficacy of this combined treatment in SCCHN has not been studied. Experimental Design: Nude mice were pretreated with control (1% Tween 80), ZD1839 (50 mg/kg) alone, celecoxib (50 mg/kg) alone, or a combination of ZD1839 and cele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 35 publications
5
109
0
1
Order By: Relevance
“…EGFR is known to induce COX-2 expression, and PGE 2 , the major end product of COX-2, is also known to activate EGFR through various pathways (1). In addition, we, as well as other researchers, have reported that inhibitors of COX-2 and EGFR can exert a synergistic antineoplastic effect when administered together in some cancer cells (16,17). Although it has been verified that the actions of COX-2 and EGFR are closely related in cells, as described above, expression patterns of COX-2 and EGFR are highly variable among cancer cell types and frequently seem to be independent of each other.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…EGFR is known to induce COX-2 expression, and PGE 2 , the major end product of COX-2, is also known to activate EGFR through various pathways (1). In addition, we, as well as other researchers, have reported that inhibitors of COX-2 and EGFR can exert a synergistic antineoplastic effect when administered together in some cancer cells (16,17). Although it has been verified that the actions of COX-2 and EGFR are closely related in cells, as described above, expression patterns of COX-2 and EGFR are highly variable among cancer cell types and frequently seem to be independent of each other.…”
Section: Introductionmentioning
confidence: 77%
“…To inhibit production of PGE 2 by COX-2, cells were treated with celecoxib, a COX-2-specific inhibitor. Celecoxib effectively blocks production of PGE 2 from COX-2 (2,5,17). Although PGE 2 production was blocked by celecoxib, EGFR expression was still down-regulated in both HCT-116-COX-2 and H460-COX-2 cells (Fig.…”
Section: Pge 2 Does Not Mediate Egfr Down-regulation By Cox-2mentioning
confidence: 87%
See 2 more Smart Citations
“…As their use in combination has been shown to block tumorigenesis in both APC Min/þ mice [34] and headand-neck carcinoma xenografted mice [35], but has not been examined for GBM, we tested the efficacy of their combination in NSC-L61, OPC-L61, hGIC1, and hGIC2. Gefitinib, an EGFR inhibitor, and Celecoxib, a Ptgs2 inhibitor, prevented the proliferation of NSC-L61, OPC-L61, and hGIC cells in a dose-dependent manner, and the combination had additive effects, although control NSCs and OPCs were also affected ( Fig.…”
Section: The Combination Of a Ptgs2 Inhibitor And An Egfr-signaling Imentioning
confidence: 99%